Budget proves govt cares, says Yahya - Bagang, Eric (Harian Ekspress (KK), 2012)
KOTA KINABALU: Deputy Chief Minister Datuk Seri Yahya Hussin said the present government is a caring and people-centric government as proven in the just announced 2013 Budget.